HUBUNGAN DAYA TARIK SPONSORSHIP DAN CITRA MEREK DENGAN KEPUTUSAN PEMBELIAN PRODUK KOSMETIK SARIAYU - Shendy Amalia, Agneta; Widowati Herieningsih, Sri (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
Sponsors are one of the marketing strategies currently chosen by companies to market their products to the wider community. The sponsorship program that has the attraction that is expected to attract the attention of the public to have the decision to buy. In addition, brand image is a strong factor to attract consumers in choosing products. The purpose of this study was to study the relationship of Sponsor attractiveness and brand image with the decision to purchase Sariayu cosmetic products. The theory used in this study is cognitive response theory and reasoned action theory. The sample technique used is Non-Probability Sampling, namely Purposive Sampling. The number of samples discussed in this study were 50 respondents with female characters domiciled in Semarang City knowing the Sariayu sponsorship program with the Miss Indonesia event and knowing Sariayu cosmetic products. Analysis of the data used in this study is the Chi-Square trial. The results of the study show that the production attracts sponsors with the purchase decision of Sariayu products having a significant relationship, the significance value and results produced after testing the Chi-Square formula with SPSS which is equal to 0,000. This is in accordance with the cognitive response theory used in this study where this theory states about the relationship of the attraction of sponsors to purchasing decisions. Furthermore, for the result image with the purchase also has a significant relationship where the significance value and results are generated after testing the Chi-Square formula with SPSS which is equal to 0,000. This is in accordance with the theory of reasoned action used in this study where this theory states about the relationship between brand image and the purchase decision of Sariayu cosmetic products.